The Perceptivity of Guests towards the In- Room Technological Amenities in Indian Hotel Industry - Anshu Rawal; Dr Sushil Kumar (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Hotel industry mainly revolves around guest and guest satisfaction. Nowadays in the hotel industry lot of facilities, services are provided to exceed the expectations of the guest staying the hotels. Hotel facilities and services like Valet Parking, in room Dining, Spa, Gymnasium, Health club, pool, multi cuisine outlets, laundry, landscape and technological amenities.